(untitled) (Colombia Medica, 1987)
Symptomatology among depressed patients has changed lately in the direction of physical symptoms. The patient is emphatic about somatic complaints, and the physician is eager to find an organic basis for these complaints. This leads to patients being subjected to exhaustive medical exams, varied somatic treatments, and even surgical interventions. In the meantime, the depressive condition worsens, for it remains unidentified.